Effects of formic acid and garlic powder on Escherichia coli in K-12 growth in raw ground beef - Martin, Randall; Kim, B.; LeMoine, K.; Magama-Moran, K.; Meyer, A.; Nave, B.; Peters, C.; Peterson, D.; Jones, Cassandra K.; Trinetta, Valentina (My University, 2017)
Introduction: Escherichia coli (E. coli) is becoming an increasingly difficult problem in meat processing facilities as well for handlers and sellers of ground meat products. There is increasing interest in new methods to combat microbial growth without affecting the final product. Purpose: The objective of this study was to observe the effects of formic acid and garlic powder on E.coli growth in ground beef. Methods: The study consisted of two samples of ground beef, one was inoculated with E.coli and one was a control. There were two separate treatments one with 1% garlic and the other with 1% formic acid. Samples were plated and enumerated for total plate counts, yeast and molds, and E.coli ; each at three different dilutions over a seven day period. Results: From all of the samples we found that this amount of garlic had no effect on any microbial growth in ground hamburger, however formic acid had a significant effect on all microbial growth in ground hamburger. Our data was calculated with a P value of less than 0.05. Our control sample of hamburger did end up getting contaminated possibly through air or poor lab practices. Significance: The results of this lab showed that the amount of garlic used had no effect however formic acid worked to significantly reduce microbial growth.
Keywords: Fall 2017